APLICAÇÃO DE ALGORITMOS GENÉTICOS PARA O PLANEJAMENTO DE GERAÇÃO DISTRIBUÍDA EM SISTEMAS DE DISTRIBUIÇÃO - Willer Oliveira, Leonardo; Rocha Oliveira, Ângelo; Vanderson Gomes, Flávio; Henriques Dias, Bruno; Chaves Silva Junior, Ivo (LINKSCIENCEPLACE, 2016)
This paper presents an approach for the planning of distributed generation (DG) resources in electrical distribution systems, comprising biomass-based thermal and wind energy. The approach determines the optimal location for placement of such generation resources aiming at minimizing energy loss, emission, investment and operation costs, in addition to the increasing of the voltage regulation and energy quality. The costs of purchasing energy from the grid and of generation from biomass are considered. The power from wind generator is given by the rated power and pre-established capacity factor. For solving the optimization problem, a genetic algorithm (GA) with embedded optimal power flow (OPF) tool to determine the optimum size of the biomass-based generators is proposed. The presented results for a system of the literature allow assess the proposed optimization approach.